(untitled) (Politeja, 2022)
The main objective of this article is to assess whether Uber should be evaluated as a profit-driven corporation hiding its destructive practices under green- -washing slogans, or as the pioneer of a new sustainable and environmentally friendly business model. Analysis of the Uber’s business model leads to the conclusion that the company deliberately benefits from hiding under the umbrellaterm of a sharing economy to attract more users and to operate in an unregulated or not-fully regulated market. Furthermore, Uber’s detrimental impact on the environment has been detailed in several European and American studies. Nevertheless, Uber has made steps away from a business model focused on service provision regardless of the environmental cost, and towards sustainably aware, low impact functioning. Uber’s ambitious Green Recovery plan of 2020 aims to start a green revolution in the ride-sharing market; however, it is questionable whether Uber will meet its own ambitious milestones.